THE INFLUENCE OF WINTER GREEN MANURES ON THE FERTILITY OF THE SOIL UNDER THE VINEYARD - Yuri V. Plugatar; Olga Е. Klimenko; Nikolai I. Klimenko; Maksim L. Novitsky (Siberian Journal of Life Sciences and Agriculture, 2023)
The paper presents data on the effect of phytoremediation: the use of a mixture of winter vetch and wheat as green manure [GM] and their combination with the microbial preparation Azotobacterin [AB] (GM +AB) in vineyard rows on soil fertility on piedmont carbonate chernozems. A variant with overgrowing of row spacing with segetal vegetation served as a control. The studies were conducted in 2018–2019 in the foothill zone of the Crimea in a vineyard founded in 2002, on grapes of cultivar ‘Bastardo Magarachsky’. Also, GM cultures were sown in November and plowed in May next year. It was found that 0.19–0.21 kg m–2 of organic matter dry mass got into the soil during the plowing with GM, 1.6 times more than in the control. Thus, GM leads to the accumulation of moisture in the layer 60–100 cm, 13.4% higher than the control, and an increase in pHH2O and active carbonates content within the permissible values for grapes. There was an accumulation of organic carbon by 0.31–0.45%, mobile forms of nutrients in the soil: NO3 - by 18%, P2O5 - by 3.2 times, K2O - by 39% in the 0–60 cm layer under the influence of GM.